Development of Crowd Simulation to Encourage Social Distancing During Convocation Ceremony - Mahmud, Arif Iskandar; Mohamad, Shamsul (Evolution in Electrical and Electronic Engineering, 2022)
The movement behaviour of the people is constantly being studied to understand and maintain human safety. During Covid19, many activities had to be carried out with physical distancing, including convocation ceremonies. Therefore, this study is to develop a simulation of crowd movement during convocation ceremonies using the Social Force Model by emphasizing the aspect of physical distancing. The results of this simulation can compare the time required to fill the hall by arranging the movement of graduates or randomly. As a result, the organized movement of graduates can be faster and comply with standard operating procedures (SOPs) set by the government, while random methods cause congestion in an area and disrupt the movement of other graduates.